ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI DI PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX PERIODE 2015-2019 - Reni Novita Sari; Diana Dwi Astuti; Nurshadrina Kartika Sari (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2021)
The purpose of this study is to determine the effect of business risk, non-debt tax shield and tangibility on capital structure with firm size as a moderating variable, by analyzing and testing. The objects in this study are companies listed on the Jakarta Islamic Index for the 2015-2019 periode. The sampling technique used purposive sampling which included 19 companies as samples. The analysis method used in this research is multiple linear regression analysis and Moderated Regression Analysis (MRA). The results showed that only business risk had an effect on capital structure, while non-debt tax shield and tangibility had no effect on capital structure. Only non-debt tax shields can be moderated by firm size and the presence of a moderating variable can strengthen the relationship between non-debt tax shields and firm size.